Nail digital dermoscopy (Onychoscopy) in the diagnosis of onychomycosis. (1st November 2011) - Piraccini, B.M.; Balestri, R.; Starace, M.; Rech, G.
Abstract: Background  Distal subungual onychomycosis and traumatic onycholysis are the most common causes of toenail abnormalities, and differential diagnosis is often impossible without mycology. Objectives  To identify and describe dermoscopic signs specific for distal subungual onychomycosis that could facilitate its diagnosis and differentiation from traumatic mycologically negative onycholysis and to determine the sensitivity and specificity of these dermoscopic features. Methods  We performed a retrospective study at the Outpatient Consultation for Nail Diseases of the Department of Dermatology of the University of Bologna. Dermoscopic digital images of 57 consecutive patients who underwent global photography, videodermoscopy and mycological examination for onycholysis of a single toenail between 1 December, 2010 and 30 June, 2011, were evaluated and compared. Digital dermoscopic images of onycholysis of the great toenail were evaluated for the presence of peculiar dermoscopic features. The presumptive dermoscopic diagnosis was compared with results of mycology. Results  Evaluation of videodermoscopic images allowed us to identify three recurring peculiar dermoscopic features, two of which were present only in distal subungual onychomycosis (jagged proximal edge with spikes of the onycholytic area and longitudinal striae) and one only in traumatic onycholysis (linear edge – without spikes – of the onycholytic area). Conclusions  We found distinctive dermoscopic signs that are exclusive to distal subungual onychomycosis and to traumatic onycholysis. Detection of these signs is simple and can, in selected cases, help to avoid mycology.